Needle-Based Confocal Laser Endomicroscopy: A New Promising Armamentarium for Diagnostic Endoscopic Ultrasound - Shah, Jimil; Rana, Surinder S (Journal of Digestive Endoscopy, 2019)
With increasing use of cross-sectional imaging in diagnosis of various diseases, incidence of asymptomatic pancreatic cyst has increased dramatically in last decade. In management of such asymptomatic pancreatic cyst differentiation of pre-malignant cyst and benign cyst remains an utmost important parameter. Though various endoscopic ultrasound (EUS) criteria have been developed, differentiation between these two entities still remains a challenge in many patients. Confocal laser endomicroscopy (CLE) has shown promising results in diagnosis of various gastrointestinal cancers and colonic polyps. However, CLE criteria have not been prospectively validated in asymptomatic pancreatic cyst to differentiate premalignant vs benign cysts. Similarly, CLE criteria are also not defined for diagnosis of various gastric sub-epithelial lesions. In this news and views we have discussed two important articles regarding role of needle based CLE (nCLE) in these lesions. While one is a multicentric trial which prospectively validates previously defined nCLE criteria for characterizing pancreatic cystic lesion, second developed criteria for diagnosis of various gastric subepithelial lesions based on nCLE findings.
Keywords: Pancreatic cystic neoplasm; Gastric sub-epithelial lesions; Endoscopic ultrasound; Gastro-intestinal stromal tumour